G Alpha-q/11 Protein Plays a Key Role in Insulin-Induced Glucose Transport in 3T3-L1 Adipocytes - Imamura, Takeshi (American Society for Microbiology, 1999)
We evaluated the role of the G alpha-q (Gαq) subunit of heterotrimeric G proteins in the insulin signaling pathway leading to GLUT4 translocation. We inhibited endogenous Gαq function by single cell microinjection of anti-Gαq/11 antibody or RGS2 protein (a GAP protein for Gαq), followed by immunostaining to assess GLUT4 translocation in 3T3-L1 adipocytes. Gαq/11 antibody and RGS2 inhibited insulin-induced GLUT4 translocation by 60 or 75%, respectively, indicating that activated Gαq is important for insulin-induced glucose transport. We then assessed the effect of overexpressing wild-type Gαq (WT-Gαq) or a constitutively active Gαq mutant (Q209L-Gαq) by using an adenovirus expression vector. In the basal state, Q209L-Gαq expression stimulated 2-deoxy-d-glucose uptake and GLUT4 translocation to 70% of the maximal insulin effect. This effect of Q209L-Gαq was inhibited by wortmannin, suggesting that it is phosphatidylinositol 3-kinase (PI3-kinase) dependent. We further show that Q209L-Gαq stimulates PI3-kinase activity in p110α and p110γ immunoprecipitates by 3- and 8-fold, respectively, whereas insulin stimulates this activity mostly in p110α by 10-fold. Nevertheless, only microinjection of anti-p110α (and not p110γ) antibody inhibited both insulin- and Q209L-Gαq-induced GLUT4 translocation, suggesting that the metabolic effects induced by Q209L-Gαq are dependent on the p110α subunit of PI3-kinase. In summary, (i) Gαq appears to play a necessary role in insulin-stimulated glucose transport, (ii) Gαq action in the insulin signaling pathway is upstream of and dependent upon PI3-kinase, and (iii) Gαq can transmit signals from the insulin receptor to the p110α subunit of PI3-kinase, which leads to GLUT4 translocation.